International Experience of Political and Legal Ensuring of Information Security under Conditions of Hybrid Warfare - Пашковський, Вячеслав Францович (Київський національний університет імені Тараса Шевченка, 2025)
The article explores international experience in the political and legal mechanisms of ensuring state information security under the conditions of hybrid warfare. It is substantiated that modern hybrid aggression creates new threats to the information space, which require a reconsideration of the state's role in the sphere of information security. It is noted that Russian aggression has contributed to the expansion of the concept of hybrid warfare and stimulated the recognition of this phenomenon as a distinct category, indicating that the aggression of the Russian Federation against Ukraine is an attempt to establish a hybrid world order, the main features of which are outlined. Effective models of NATO member states, EU countries, and several others are demonstrated in responding to information threats, based on interagency coordination and regulatory frameworks. It is argued that the implementation of international experience into national practice requires adaptation, taking into account the specific features of the political system and security environment. International cooperation and information exchange are key factors in enhancing the effectiveness of political and legal support for information security under hybrid warfare conditions. The main vectors of transformation of political and legal mechanisms for ensuring information security in the context of hybrid warfare are identified, including: strengthening interagency coordination; development of strategic communications infrastructure; creation of a unified crisis response system to information attacks; integration of cybersecurity into the political process; transition to a model of “proactive information security.” These vectors must be implemented based on a coherent state policy.

У статті розглядається міжнародний досвід політико-правових механізмів забезпечення інформаційної безпеки держави в умовах гібридної війни. Обґрунтовано, що сучасна гібридна агресія створює нові загрози інформаційному простору, які вимагають переосмислення ролі держави у сфері інформаційної безпеки. Зазначено, що російська агресія спонукала до розширення змісту гібридної війни, стимулювала процес осмислення цього явища як окремого феномена, який свідчить, що агресія РФ проти України є спробою формування гібридного світоустрою та з'ясовано основні його показники.Продемонстровано ефективні моделі Країни НАТО, ЄС, деяких інших країн по реагування на інформаційні загрози, що базуються на міжвідомчій координації та нормативній базі. Стверджується, що впровадження міжнародного досвіду в національну практику вимагає адаптації з урахуванням особливостей політичної системи та безпекового середовища, що міжнародна співпраця та обмін інформацією є ключовими факторами підвищення ефективності політико-правового забезпечення інформаційної безпеки в умовах гібридної війни. Визначено основні вектори трансформації політико-правових механізмів забезпечення інформаційної безпеки в умовах гібридної війни, серед яких: посилення міжвідомчої координації; розвиток інфраструктури стратегічних комунікацій; створення єдиної системи кризового реагування на інформаційні атаки; інтеграція кібербезпеки до політичного процесу; перехід до моделі "проактивної інформаційної безпеки". Ці вектори мають бути реалізовані на основі узгодженої державної політики.
Міжнародний досвід політико-правового забезпечення інформаційної безпеки в умовах гібридної війни
Keywords: information security; hybrid warfare; state policy; strategic communications; national security; political and legal mechanisms; інформаційна безпека; гібридна війна; державна політика; стратегічні комунікації; національна безпека; політико-правові механізми